Prevalence of post-acute coronavirus disease 2019 symptoms twelve months after hospitalization in participants retained in follow-up: analyses stratified by gender from a large prospective cohort. (February 2023) - Ghosn, Jade; Bachelet, Delphine; Livrozet, Marine; Cervantes-Gonzalez, Minerva; Poissy, Julien; Goehringer, François; Gandonniere, Charlotte Salmon; Maillet, Mylène; Bani-Sadr, Firouzé; Martin-Blondel, Guillaume; Tattevin, Pierre; Launay, Odile; et al.
Abstract: Objectives: Persistent post-acute coronavirus disease 2019 (COVID-19) symptoms (PACSs) have been reported up to 6 months after hospital discharge. Herein we assessed the symptoms that persisted 12 months (M12) after admission for COVID-19 in the longitudinal prospective national French coronavirus disease cohort. Methods: Hospitalized patients with a confirmed virological diagnosis of COVID-19 were enrolled. Follow-up was planned until M12 after admission. Associations between persistence of ≥3 PACSs at M12 and clinical characteristics at admission were assessed through logistic regression according to gender. Results: We focused on participants enrolled between 24 January 2020 and 15 July 2020, to allow M12 follow-up. The M12 data were available for 737 participants. Median age was 61 years, 475 (64%) were men and 242/647 (37%) were admitted to intensive care units during the acute phase. At M12, 27% (194/710) of the participants had ≥3 persistent PACS, mostly fatigue, dyspnoea and joint pain. Among those who had a professional occupation before the acute phase, 91 out of 339 (27%) were still on sick leave at M12. Presence of ≥3 persistent PACS was associated with female gender, both anxiety and depression, impaired health-related quality of life and Medical Muscle Research Council Scale <57. Compared with men, women more often reported presence of ≥3 persistent PACSs (98/253, 39% vs. 96/457, 21%), depression and anxiety (18/152, 12% vs. 17/268, 6% and 33/156, 21% vs. 26/264, 10%, respectively), impaired physical health-related quality of life (76/141, 54% vs. 120/261, 46%). Women had less often returned to work than men (77/116, 66% vs. 171/223, 77%). Conclusions: One fourth of the individuals admitted to hospital for COVID-19 still had ≥3 persistent PACSs at M12 post-discharge. Women reported more often ≥3 persistent PACSs, suffered more from anxiety and depression and had less often returned to work than men.